2008
DOI: 10.1111/j.1469-7998.2008.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Home range and habitat selection of pampas deer

Abstract: The southernmost subspecies of pampas deer Ozotocerus bezoarticus celer is an endemic and endangered cervid of the Argentine Pampas. The aim of our study was to describe the habitat use of this deer on the coast of Samboromb´on Bay. Twelve adult pampas deer (seven female and five male) were radiotracked and their home-range sizes and habitat selection studied from 1995 to 2001. The mean home-range size was 898 AE 181 ha, and the core area was concentrated in 22% of their range. The home-range size of males was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
0
13
0
13
Order By: Relevance
“…Similarity of forage resource use was lowest between the pampas deer and the two other herbivores. However in a study in the Argentinean pampas Vila et al (2008) showed that habitat selection by pampas deer was affected by cattle presence, and pampas deer were usually encountered in areas without cattle. In this study pampas deer were observed to use similar areas as cattle and generally fed nearby.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarity of forage resource use was lowest between the pampas deer and the two other herbivores. However in a study in the Argentinean pampas Vila et al (2008) showed that habitat selection by pampas deer was affected by cattle presence, and pampas deer were usually encountered in areas without cattle. In this study pampas deer were observed to use similar areas as cattle and generally fed nearby.…”
Section: Discussionmentioning
confidence: 95%
“…In Patagonia, livestock competes with guanaco (Lama guanicoe) (Baldi et al, 2004). Many authors have voiced concern regarding the impact of livestock grazing on native wildlife and this issue remains a matter for considerable debate (Fleischner, 1994;Baldi et al, 2004;Lamprey and Reid, 2004;Chaikina and Ruckstuhl, 2006;Vila et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Introduced livestock have competed directly for food resources with all three species, and indirectly through the transmission of their diseases to native animals (Uhart et al 2003;Vila et al 2008). This has led to disruption of original geographical distributions, range reductions and local extinction (Real et al 2003).…”
Section: Other Vertebratesmentioning
confidence: 99%
“…It is broadly demonstrated that cattle and sheep grazing changes species composition, decreases the contribution of dominant species, and may increase bare soil at higher stocking rates (Bakker et al, 1985;Andresen et al, 1990;Bouchard et al, 2003;Kleyer et al, 2003). On the contrary, in South American salt marshes, grazing by domestic herbivores is quite recent and, consequently, the study of grazing effects is scarce and focused on native small herbivores (Jackson and Giulietti, 1988;Bortolus and Iribarne, 1999;Cardoni et al, 2007;Vila et al, 2008). Recent information about cattle grazing on Spartina densiflora salt marshes of Argentina suggests that vegetation cover decreases as grazing intensity increases (Isacch and Cardoni, 2011) and that continuous grazing reduces forage quality and increases soil salinity (Di Bella et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The vegetation is a brackish community dominated by S. densiflora, which occupies the upper levels of the intertidal area and is overflowed during high tides (Isacch et al, 2006). These salt marshes have been sporadically grazed by cattle at low stocking rates (Isacch et al, 2004;Vila et al, 2008) but, over the past decade, agriculture expansion in the temperate humid region of Argentina led to a displacement of livestock to more marginal areas, such as the Samborombon Bay. Consequently, these salt marshes are currently subjected to higher grazing pressure than that historically applied.…”
Section: Introductionmentioning
confidence: 99%